The effect of business ecosystem and government regulation toward business agility: the role mediating of business model innovation in SMEs - Ervina Waty; Idris Gautama So; Richardus Eko Indrajit; Sri Bramantoro Abdinagoro (President University, 2022)
SMEs have become the backbone of the Indonesian economy which is faced with various situations and conditions. The increasingly competitive business environment forces SMEs to be able to maintain their existence. This effort can be realized by developing a good business ecosystem with the support of government regulations. In addition, business model innovation is also worth considering the changing needs, wants, and demands of customers. This study aims to examine the effect of ecosystem business and government regulation toward business agility mediated by business model innovation. This study involved 100 SME culinary in Bali, Bandung, Surabaya, Yogyakarta, Semarang, Solo dan Jakarta which are selected using probability sampling technique. Data is obtained by distributing questionnaires to respondents through G-Form. The collected data is then analyzed using Path analysis assisted by the Smart PLS application. The result shows that the business ecosystem and government regulation and business model innovation have a significant positive effect toward business agility. Business model innovation can mediate the relationship of the business ecosystem to business agility and the relationship of government regulation to business agility. Business model innovation is influenced by Business ecosystem and Government Regulation by 68.8%, business ecosystem, Government Regulation and business model innovation affects business agility by 61.6%. Researchers who want to conduct research on similar topics can add other independent and dependent variables so that the results obtained are more coherent.